Karakteristik Gambaran CT Scan Toraks Pasien HIV Berdasarkan Nilai CD4 - Armelia Adel Abdullah; Redo Widhio Mahatvavirya (Universitas Prima Indonesia, 2023)
A decreased CD4 count in HIV patients will result in decreased immunity, making it easier for opportunistic infections to occur. The lower the CD4⁺ value, the more likely an abnormality will be found on the chest X-ray. In Indonesia, no published research has been conducted on CT scans of the chest in HIV patients, so it is not yet known whether the CT scan characteristics of HIV patients in Indonesia are the same as those in other countries. The purpose of this study was to assess the characteristics of the CT scan of the chest and its relationship to CD4⁺ degrees with the hope that it could enhance the role of CT scan of the chest as a reliable examination. This study is a prospective cross-sectional study to assess the relationship between CD4⁺ score and CT scan characteristics of the chest. Data collection was carried out at the Radiodiagnostic Installation of Persahabatan Hospital Jakarta from August 2018 to January 2019, using a consecutive sampling technique, namely data collection based on inclusion and exclusion criteria. There were 50 research subjects, 12 women and 38 men, the majority aged >41 years. Variation of chest CT scan images in HIV patients where infiltrates are seen is the most common chest radiographic appearance in study subjects in both the CD4⁺ <200 group and the CD4+ ≥ 200 group. Almost the same number of atypical and atypical features in the group with CD4⁺<200 values, whereas in the group with CD4⁺⁺ ≥200 the typical picture was much more than atypical. Based on the location distribution, in patients with CD4⁺<200 values, infiltrates were more often found in the midfield and lung bases, while patients with CD4⁺⁺200 values ​​were mostly in the upper field. In conclusion, there is no significant difference between typical and atypical descriptions